Perbandingan Financial Distress Sebelum dan Selama Covid-19 pada Perusahaan Sektor Property dan Real Estate Terdaftar Indeks Saham Syariah Indonesia (ISSI) - Maghfira Musdalifah Melania Islami; Clarashinta Canggih (Jurnal Ilmiah Ekonomi Islam, 2023)
This study aimed to compare the financial distress of property and real estate sector companies that were listed on the Indonesian Sharia Stock Index before and during Covid-19. The study was comparative quantitative by comparing the data used to determine differences in variables from two groups or the same variable in different time periods. The number of samples used in this study were 31 companies, with the sample collection method in the form of purposive sampling. The data analysis method used is the Altman Z-Score method using four financial ratios taken from the Indonesia Stock Exchange website and the sites of each sample company. The data analysis were the normality test and the Wilcoxon test. This study found that there were significant differences in the level of financial distress in property and real estate sector companies listed on the Indonesian Sharia Stock Index before and during Covid-19.